KEMAMPUAN REPRESENTASI MATEMATIS MENYELESAIKAN SOAL SEGI EMPAT DITINJAU DARI SELF-EFFICACY DI MADRASAH TSANAWIYAH - Ni Ketut A Ariutari Pratiwi; Edy Yusmin; Ahmad Yani T (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis research aims to determine how the ability of mathematical representation of students solve quadrupests that have self-efficacy high, moderate, and low, in class VIII at Mts Mathla'ul Anwar Pontianak. The research method is qualitative descriptive research, the data collection techniques used are test techniques and direct communication techniques. The data collection tools used are polls, problems with Essai, and interviews. It is obtained that students with high self-efficacy can relatively understand the context of the problem, can present the information provided in visual, verbal and symbol forms; Self-efficacy students are having difficulties in resolving the given problem, unable to represent the complete and less precise representation, and still confusion in the representation of representations to be used so that Understand the context of the matter; Students with self-efficacy low difficulty in resolving the problem, do not understand the context of the given problem, can not determine and represent the representation correctly.  Keywords: Ability of Represenasi Matematis, Rectangular, Self-Efficacy